2023
DOI: 10.3389/fneur.2022.1052401
|View full text |Cite
|
Sign up to set email alerts
|

Is the female sex associated with an increased risk for long-term cognitive decline after the first-ever lacunar stroke? Prospective study on small vessel disease cohort

Abstract: BackgroundSex is a significant determinant of survival and functional outcome after stroke. Long-term cognitive outcome after acute lacunar stroke in the context of sex differences has been rarely reported.MethodsA cohort of small vessel disease (SVD) patients presenting with first-ever acute lacunar stroke and normal cognitive status has been evaluated 4 years after the qualifying event for the presence of cognitive impairment (CI) with a comprehensive neuropsychological battery. Differences in baseline clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Considering stroke patients and the view that depression leads to cognitive impairment, post-stroke depression has been associated with worse performance in cognitive functions, including inhibition/switching errors [46], memory [56,57], reduced psychomotor/cognitive speed [57,58], nonverbal problem solving, and attention [57]. Considering the impact of gender, women who have experienced lacunar strokes have been found to have cognitive impairment more frequently than men, and this association has been shown to be dependent on the occurrence of depression and severity of white matter hyperintensities in women but not in men [59]. In line with that, with regard to specificity, our results suggest that, after stroke, there may be a correlation between changes over time in depressive symptom severity and changes in phonemic verbal fluency in women, but not in men.…”
Section: Discussionmentioning
confidence: 99%
“…Considering stroke patients and the view that depression leads to cognitive impairment, post-stroke depression has been associated with worse performance in cognitive functions, including inhibition/switching errors [46], memory [56,57], reduced psychomotor/cognitive speed [57,58], nonverbal problem solving, and attention [57]. Considering the impact of gender, women who have experienced lacunar strokes have been found to have cognitive impairment more frequently than men, and this association has been shown to be dependent on the occurrence of depression and severity of white matter hyperintensities in women but not in men [59]. In line with that, with regard to specificity, our results suggest that, after stroke, there may be a correlation between changes over time in depressive symptom severity and changes in phonemic verbal fluency in women, but not in men.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence suggesting that there may be sex differences in the susceptibility to and outcomes of cerebral ischemia. Several preclinical studies have reported differences in brain damage, neuroinflammation, and neuroprotective responses between male and female animals exposed to ischemic insult [112,113]. Investigating these sex differences may lead to the development of sex-specific therapeutic strategies for the prevention and treatment of global cerebral ischemia.…”
Section: Challenges and Future Directions For In Vivo Models Of Cereb...mentioning
confidence: 99%
“…1 Females have been reported to be more susceptible than males to CSVD and its effect on cognition. 1,2 Sex-specific variations in how several vascular risk factors such as hypertension affect CSVD have also been reported. Hypertension, which increases with age, is an established risk factor for cerebrovascular conditions, which are prominent causes of morbidity and mortality.…”
mentioning
confidence: 99%